Comparing Diagnostic Accuracy of Minimum Rim Width (MRW) and Retinal Nerve Fibre Layer (RNFL) in Detection of Glaucoma (Medical Forum Monthly, 2024)
Objective: To evaluate and compare the diagnostic accuracy of minimum rim width and Retinal Nerve Fiber Layer in detection of glaucoma by taking cup-to-disc ratio as gold standard.Study Design: Descriptive observational studyPlace and Duration of Study: This study was conducted at the Ophthalmology department of Ghazi Hospital Dera Ghazi Khan from March 2022 to August 2022.Methods: The study enrolled healthy individuals and those identified as glaucoma suspects based on criteria such as cup-to-disc ratio or elevated intraocular pressure exceeding 21 mmHg, who were attending the eye clinic. Main variables of study were co-morbidities (diabetes and hypertension), cup to disc ratio, diagnostic accuracy, sensitivity and specificity.Results: A total of 300 patients were enrolled. There were 96.3% patients diagnosed with glaucoma by using cup to disk ratio, 85.3% were diagnosed with glaucoma by using RNFL and 87.7% patients diagnosed with glaucoma by using MRW. Sensitivity was 87.9%, 90.3%, specificity 81.8%, 81.8%, PPV 92.2%, 92.2%, NPV 20.5%, 24.3% and accuracy 87.7%, 90% of RNFL and MRW with cup to disk ratio using as a gold standard.Conclusion: The diagnostic sensitivity for glaucoma is higher with retinal nerve fiber layer (RNFL) measurements compared to minimum rim width (MRW), but the specificity is equal for both. In myopic eyes, Bruch’s membrane opening minimum rim width is comparable to RNFL thickness, making it a valuable diagnostic tool for identifying glaucoma in patients with myopic optic discs.